Burstable nanostructured micro-raspberries: Towards redispersible nanoparticles from dry powders - Stauch, Claudia; Ballweg, Thomas; Stracke, Werner; Luxenhofer, Robert; Mandel, Karl (Journal of Colloid and Interface Science, 2017)
Despite immense progress in nanoscience and technology, one of the yet unsolved challenges is the redispersion of nanoparticles from dry powders back to the individual, primary particles. Herein, an easy to handle powder consisting of nanostructured micron sized raspberry-like particles is presented. These nanostructured micro-raspberries are composed of individual nanoparticles which are equipped with molecules that introduce a separating effect or “spring” functionality. Thereby, a powder system is obtained that allows for an easy and complete redispersibility of the agglomerates down to the level of individual nanoparticles in solvents and polymers. The mechanism of redispersibility involves mechanic stimuli/force as well as solvent like disintegration aspects (“like dissolves like” effect). Furthermore, by tailoring the degree of spacer-equipped particles, the bursting behavior can also be tuned, yielding different redispersion degrees. The redispersibility of the nanostructured micro-raspberries is demonstrated in solvents and silicone-based nanocomposites.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Nano dispersions; Nano powders; Nanostructured micro-raspberries; Redispersible agglomerates; Redispersible nanoparticles